Priorities and Challenges for Cancer Prevention and Surveillance - Silva, Gulnar Azevedo e (2025)
The editorial focuses cancer burden in Brazil and worldwide, contextualizing the major issues involved in the estimates of incidence of the several types and scientific knowledge acquired so far in terms of prevention. It highlights the necessity to invest in public health actions that should be considered by the political and health authorities. Introduces arguments that strengthen the construction of a cancer prevention and control policy grounded on the existence of several etiologic pathways resulting from the accumulation and integration of exposures to different lifelong risk factors. Based on the well-succeeded experience with tobacco control in Brazil, it indicates the importance of controlling prevalent modifiable risks exposure with effective prevention strategies supported by epidemiologic studies that address socioeconomic inequalities and allow future comparisons and improvement of health surveillance.